N-heterocyclic carbene-catalyzed stetter reaction and related chemistry - Mondal, Santigopal; Yetra, Santhivardhana R.; Biju, Akkattu T. (N‐Heterocyclic Carbenes in Organocatalysis, 2019)
The reversal of normal mode of reactivity (umpolung) of aldehydes is the most important application of N-heterocyclic carbenes (NHCs) in organocatalytic transformations. The benzoin condensation and the Stetter reaction are the two historic reactions where NHC reacts with aldehyde to generate acyl anion equivalent, which is subsequently intercepted with another molecule of carbonyl compound or Michael acceptor leading to the formation of the benzoin/Stetter products. The objective of this chapter is to provide an overview on NHC-catalyzed Stetter reaction and related chemistry. The development of various chiral catalysts for enantioselective intra- or intermolecular Stetter reaction has been described. Additionally, recent progress on NHC-catalyzed addition of aldehyde to unactivated multiple bonds in the hydroacylation reaction has been demonstrated.